Problematyka dozoru ochronnego nad warunkowo skazanymi w polskim prawie karnym: [The probation system in Polish criminal law] (Studia Prawnicze / The Legal Studies, 2023)
Probation is at the present time one of the chief methods of dealing with the criminal offender by the State in its constant endeavours to make the punishment fit the individual crime. Probation has a two-fold purpose — in the first place to protect the chance offender from coming into contact with hardened prison inmates, and in the second place not only to prevent the further demoralization of the offender but also to lead to an improvement in his behaviour. Therefore in ordering probation, the court should not only consider whether the offender is likely to improve without a term of imprisonment, and suspend punishment if it thinks so, but should also issue dispositions that will lead to a real improvement in the offender’s behaviour. This can only be done if the offender, instead of being deprived of his liberty is subjected to other educative influences. For example, the court may impose certain conditions on the convicted person, and order him to be placed under the supervision of a probation officer for a certain period. This last measure is undoubtedly of prime importance, since it not only provides a check on the offender, but also gives him the indispensible support of a person to guide and advise him. Supervision is therefore the principal factor which determines the effectiveness or otherwise of the probation. The first part of the paper (Introductory remarks) explains how supervision determines the effectiveness of the probation system. The second part of the paper, headed „development of legislation and doctrine” describes the growth of the probation movement in Poland from 1918 up to the present day as regards theory, legislation, and the measurement of justice. In Polish legal literature probation is mentioned as far back as the eighties of last century, when Polish writers report the introduction of the probation system in the English speaking countries and recommend its adoption in Poland. There was a marked increase of interest in this problem when Poland gained her independence at the end of the first World War. The Criminal Code, enacted in 1932, which unified and replaced the previous criminal law of the Partition Powers, introduced wide rules on suspension of the execution of sentence and authorized the courts to place an offender whose sentence had been suspended, under the supervision of a „trustworthy person or institution”.Between 1932 and 1939, however, this regulation was not put into practice by the Polish courts, for during this period no State or social bodies were set up to exercise such supervision.After the second World War, the regulation on probation was in abeyance until 1961. For it was not until that year that the Minister of Justice issued an order creating for the first time in Poland the necessary machinery for a probationary system. Following this order, the probation officer were attached to every voivodship and district court. The probation officers carry out their duties on a voluntary basis. Their rights and duties are prescribed by the order, which also defines the duties of the offender towards the probation officer. It also fixes the way supervision may be entrusted to bodies such as places of employment or social organizations.In the second half of 1961 the courts began to put offenders on probation and give them into the care of the voluntary probation officers. This practice, however, did not spread as was expected. Quite the contrary, for between 1962 and 1964 the number of persons given into the care of a probation officer decreased steadily. At the same time it should be noted that suspension of the execution of sentence became more and more common. So the probationary supervision of offenders, the execution of whose sentence has been suspended, is still in the experimental stage and in actual practice does not play any great part in the execution of justice.The third part of the paper proposes certain changes in the legislation, especially concerning those elements of suspension of execution of sentence which really decide whether the probation is effective or not. In this part of the paper the author also discusses the draft of the Criminal Code that was published in 1963.The main conclusions reached by the author are that much more should be done to exert an educative influence on the offender during the probation period. He particularly advocates building up a fixed system of conditions which must be fulfilled if the probation period is to be completed successfully. He points out, however, that the law must enumerate these duties taxatively. During the probation period the court should have the right to impose new conditions on the probationer or free him from some conditions, or shorten or lengthen the period of probation.The author is in favour of employing professional and suitably qualified personnel as probation officers, although probationers may also be entrusted to individual voluntary officers or institutions representing the offender’s environment.Comments are also made on the course of the probation period, its termination, pre-sentence investigation, and the financial aspect of probation. The paper closes with remarks on the form of the legal acts that regulate the course of the probation period. The author would like to see a special statute governing this problem, which would be an extension of the basic points contained in the future Criminal Code.